Theoretical Investigations on spray travel of gas cooler - Rao, B Nageswara; Reddy, K Vijaya Kumar (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Spray cooler with water droplets as a spray liquid is having extensive applications in industries and scientific organizations to cool exhaust hot gases without any hot spots. The cooling occurs as a result of the direct injection of water into the cooler chamber. Water injected at high pressure is atomized into fine spray and as the droplets of the spray travel along the length of the spray cooler. Up to a particular length of the cooler, heat is transferred from the hot combustion gases to the water droplets and water evaporates from the surface of the droplet and diffuses into the hot gas. If the cooler length is more, the gas temperature will be sufficiently low and condenses the moisture present in the hot gas. In the present research paper, a 3D model of the spray cooler is considered for the numerical investigations to optimize the spray cooler length for effective cooling with minimum unevaporated droplets.